APLIKASI MENENTUKAN JENIS PERMAINAN UNTUK PERKEMBANGAN ANAK USIA 0-6 TAHUN - Elyza Gustri Wahyuni; Erna Retno Wukiratun (Teknoin, 2017)
Growing up in children is one aspect that is taken seriously by the parents, because it is an aspect related to the formation of a person. The role of parents for child growth can also affect how their children develop. Parents have different ways of caring for their children and the games provided do not help the child's development be more optimal. Children who are detected to experience developmental delay need special attention, therefore training children through suitable and appropriate games can improve their development. So it takes an expert system of early detection to determine the type of game that is in accordance with the development of gross motor, fine motor, language, and social behavior in children aged 0 to 6 years. The results of this study indicate that the type of game that is applied as an exercise for child development is appropriate and can be used to assist in improving child development optimally.